Pengaruh Online Customer Rating, Online Customer Review, dan Gratis Ongkos Kirim Terhadap Keputusan Pembelian di Marketplace Shopee (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis UNISMA) - Alivia, Putri Sabna Naza; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine and analyze the effect of online customer rating, online customer review , and free shipping on consumer purchasing decisions at the Shopee marketplace. This research uses a case study on active students of the Faculty of Economics and Business, Islamic University of Malang who were selected by purposive sampling. Determination of the number of samples using the Malholtra formula and the results obtained were 65 respondents.  The data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis Test (F test and t test), and Test Coefficient of Determination (Adjusted R2). The analysis process uses SPSS. The results of the study state that online customer rating, online customer review , and free shipping simultaneously affect purchasing decisions and partially online customer rating, online customer review , and free shipping have a positive and significant effect on purchasing decisions. Keywords: Online Customer Rating, Online customer review, Free Shipping, and Purchasing Decision